Innovation generation : how to produce creative and useful scientific ideas - Ness, Roberta B. (Oxford University Press, USA, 2012)
"Whether you are a student or an established scientist, researcher, or engineer, you can learn to be more innovative. In Innovation Generation, internationally renowned physician and scientist Roberta Ness provides all the tools you need to cast aside your habitual ways of navigating the every-day world and to think "outside the box." Based on an extraordinarily successful program at the University of Texas, this book provides proven techniques to expand your ability to generate original ideas. These tools include analogy, expanding assumptions, pulling questions apart, changing your point of view, reversing your thinking, and getting the most out of multidisciplinary groups, to name a few. Woven into the discussion are engaging stories of famous scientists who found fresh paths to innovation, including groundbreaking primate scientist Jane Goodall, father of lead research Herb Needleman, and physician Ignaz Semmelweis, whose discovery of infection control saved millions. Finally, the book shows how to combine your newly acquired skills in innovative thinking with the normal process of scientific thinking, so that your new abilities are more than playthings. Innovation will power your science"--Provided by publisher.
Keywords: Creative ability in science.; Science -- Study and teaching.; Creative thinking -- Study and teaching.; Creative ability.; Science.; elektronické knihy; electronic books